Deradikalisasi Penafsiran Al-Qur'an dalam Konteks Keindonesiaan yang Multikultur - Mustaqim, Abdul (SUHUF, 2013)
It is recognized that in the QurÃ¢â‚¬â„¢an, there are verses that are textually have the potential to encourage violence acts. The idea of the importance of de-radicalization is related to the commentary of the QurÃ¢â‚¬â„¢anic verses that seem to be "radicalÃ¢â‚¬Â is very important in order that someone is not driven to commit violence in the name of religion. It is because, somehow, the product of the commentary of the QurÃ¢â‚¬â„¢an plays a role in providing the color of the understanding of Islam to society. To reaffirm the shady face of Islam, which is polite, tolerant, and peace should be a mutual commitment without losing the prestige and value in the eyes of the other community. This writing tries to give a new paradigm in understanding the verses of the text of which are considered to be "radicalsÃ¢â‚¬Â and potentially trigger the violence acts.Keywords : radical, de-radicalization, The commentary of the Quran, multi-culture